"We are on air now": the emotionality of video-recording in the institutional setting. Issue 4 (4th July 2017) - Wilińska, Monika; Bűlow, Pia H.
Abstract: This article engages with the practice of video recording in social research. We draw on our research of institutional talk to explore the emotionality of video recording in the context of the studied situations. Drawing on insights from Collins' theory of interaction rituals, we demonstrate a variety of situational moments in which different participants negotiate the presence of a video camera. Our analysis reveals the emotional aspects of negotiating and appropriating the presence of such technologies by all parties involved in the research process. We contribute to and extend the growing body of literature that discusses the meaning of technology for social research by emphasizing the emotionality of using video cameras in social and research practices.